Effects of dynamic gate pouring on casting's filling and feeding capacity. Issue 5 (4th April 2017) - Yao, Shan; Wang, Tingli; Sui, Longfei; Tong, Qiang; Jiao, Yinan
ABSTRACT: Dynamic gate pouring means the liquid is poured by a submerged gate that can be moved vertically in synch with the rising of the free surface of the liquid metal in the mold. In this paper, the filling capacity and the feeding capacity of the fixed gate pouring (top pouring and bottom pouring) and the dynamic gate pouring methods were investigated. By top pouring method, the fluid flow was turbulent during the filling process, which would bring turbulent fluidity length results. It roughly had higher temperature in the higher region at the end of filling, which was beneficial to improve the feeding capacity. By bottom pouring method, the free surface of the liquid metal in the mold was smooth from the bottom to the top, and the liquid metal temperature decreased with the rise of the liquid level, which would decrease the filling capacity and the feeding capacity. By dynamic pouring method, the liquid metal in the mold rose up slowly and smoothly during the filling process, and it had higher temperature in the higher region, which could promote the filling capacity and the feeding capacity.